Edukasi Post Stroke pada Lansia di Desa Kasang Kumpeh - Mawaddah Warahmah; Indah Permata Sari (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Old age or eldery must occur in the human condition. Various types of diseases are very easy to attack the function of our body organ. To minimize the disease that comes, a good lifestyle is needed by means of regular exercise and education about health awareness. Stroke is the third most common cause of death in developed countries after cardiovascular disease and cancer. Community service activities are carried out in September - December 2021 by providing educational leaflets and outreach to the elderly or post-stroke patients about strengthening exercise and balance exercise education. Strengthening exercise and balance exercise educational activities for post-stroke patients in Kasang Kumpeh Village are activities provided so that the elderly can understand and apply in daily activities so that activities are not limited. Aims for limited movement to walk normally and daily activities can be done independently. This Community Service (PKM) aims to be used as a source of knowledge for the elderly for post-stroke therapy for the elderly in the village of Kasang Kumpeh. The results of the evaluation both through questions and answers and post-stroke education are that the average elderly can understand the directions so that they can reduce the number of elderly people who have a stroke.